ANALISIS PRODUK DAN HARGA TERHADAP KEPUTUSAN MAHASISWA UNIVERSITAS IGM MEMBELI SMARTPHONE SAMSUNG - Dwi Irawan; Luis Marnisah; Azrai’e K.Rosni (Universitas Indo Global Mandiri)
The purpose of the study was to find out how was the analysis of resultsbetween product and price of IGM University Students’ Decisions in purchasing Samsung smartphone. The population taken consisted of 1136 respondents. One hundred of them were selected as the sample by using slovin formula. In this study, descriptive analysis by applying quantitative method was used, then questionnaire was distributed as a technique for collecting the data, and simple linear regression analysis was applied in order to measure the effect of independent variable to dependent variable which were Marketing Mix (X) was considered as an independent variable and students’ decisions (Y) as a dependent variable. In analyzing the data, Microsoft Office Excel program was used and it had been tabulated. Finally, the result of the study showed that the marketing mix abautanalycis of Product and Price had a significant effect on the IGM University students’ decisions in purchasing the Samsung smartphone.Keywords: Product and Price in taking decision of purchasing, quantitative methods